What she said the art of inspiring action through speech - Lunin, Monica (John Wiley and Sons Australia, Ltd, 2022)
Learn how spoken words can change a mind, a community and the world with this collection of remarkable speeches by women. What She Said is an inspiring collection of speeches from passionate and persuasive women from around the world and throughout history. The included speakers come from diverse cultural and ethnic backgrounds, ages, and education levels, demonstrating how women from all walks of life can use the power of speech to bring change. Author Monica Lunin has curated and analysed 40 of the greatest speeches made by strong and empowering women from all around the world. From Queen Elizabeth I to Maya Angelou, Greta Thunberg, Julia Gillard, and Michelle Obama, What She Said shows not only what was said but also how the speech worked and why it was effective. In this insightful exploration of female wit, persuasion, and leadership, you'll find an extract of the speech, a biography of the speaker and a breakdown of the qualities that made it so remarkable. --Provided by publisher.